2004
DOI: 10.1242/jcs.00899
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-mediated folding and assembly of myosin in striated muscle

Abstract: De novo folding and assembly of striated muscle myosin was analyzed by expressing a GFP-tagged embryonic myosin heavy chain (GFP-myosin) in post-mitotic C2C12 myocytes using replication defective adenoviruses. In the early stages of muscle differentiation, the GFP-myosin accumulates in bright globular foci and short filamentous structures that are later replaced by brightly fluorescent myofibrils. Time-lapse microscopy shows that the intermediates are dynamic and are present in elongating and fusing myocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 43 publications
5
131
0
Order By: Relevance
“…The participation of UNC-45b in intermolecular complexes with either cardiac myosin or GATA4 was shown by pull-down experiments with cell lysates. The direct binding between UNC-45b and GATA4 was further confirmed by binding experiments with purified components as has been shown previously for myosin Srikakulam and Winkelmann, 2004;Srikakulam et al, 2008). The luciferase reporter assay indicated that GATA4-mediated transcriptional activation was enhanced by UNC-45b.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The participation of UNC-45b in intermolecular complexes with either cardiac myosin or GATA4 was shown by pull-down experiments with cell lysates. The direct binding between UNC-45b and GATA4 was further confirmed by binding experiments with purified components as has been shown previously for myosin Srikakulam and Winkelmann, 2004;Srikakulam et al, 2008). The luciferase reporter assay indicated that GATA4-mediated transcriptional activation was enhanced by UNC-45b.…”
Section: Discussionsupporting
confidence: 79%
“…This gene is also expressed in skeletal muscle and is closely related to orthologs in vertebrate organisms from zebrafish to humans. Studies with C. elegans, cultured myocytes and purified muscle proteins have shown the significance of UNC-45b functioning in the myofibrillogenesis and maturation of full contractile functions in multiple striated muscles (Barral et al, 1998;Barral et al, 2002;Hutagalung et al, 2002;Price et al, 2002;Srikakulam and Winkelmann, 2004;Srikakulam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that muscle myosin filaments assemble separately from nascent Z-bodies and actin filaments [35]. Recent studies have shown that nascent myosin filaments are associated with the chaperone proteins Hsc70 and Hsp90 before incorporation into sarcomeres [36] ( figure 10, step 2). The accumulation of abnormally thin striated myofibrils after Krp1 knockdown shows that Krp1 functions downstream of N-RAP, Hsc70 and Hsp90 in the assembly pathway to promote lateral fusion of thin myofibrils ( figure 10, step 4).…”
Section: Krp1 Promotes Lateral Fusion Of Myofibril Assembly Intermedimentioning
confidence: 99%
“…Areas rich in folding intermediates were selected and marked on the dishes. Samples were dehydrated through a serial dilution of graded alcohol, embedded in Epon and sectioned with a diamond knife (Srikakulam and Winkelmann, 2004). Thin sections were stained in uranyl acetate and lead citrate, and examined by a JEOL JEM1010 electron microscope operated at 80 kV.…”
Section: Electron Microscopymentioning
confidence: 99%